Campyloneura Lengersdorf, 1939 - eine ’vergessene’ Lestremiinen-Gattung wiederentdeckt (Diptera, Cecidomyiidae, Lestremiinae). - Jaschhof, Mathias; Menzel, Frank (Contributions to Entomology = Beiträge zur Entomologie, 1995)
Being founded on the holotype the authors give a redescription of Campyloneura recondita Lengersdorf, 1939, a species which has never mentioned again since it was described. As the genotype recondita shows all characters of the genus Polyardis Pritchard, 1947. That name becomes a later synonym of Campyloneura Lengersdorf.